In Service of the Lowly Nazarene Carpenter: The English Canadian Labour Press and the Case for Radical Christianity, 1926–1939 - Aivalis, Christo (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2014)
This article examines some of Depression-era Canada’s most influential labour newspapers with the intent to show that their writers were deeply inspired by radical Christianity. While connected in many ways to earlier strands of working-class and leftist Christianity as typified by the social gospel, radical Christianity differs in the extent to which the roots of social dysfunction were acknowledged as being linked to the capitalist order, and the solution being in its destruction. In this way, one can find deep intellectual connections between the Canadian labour press and the members of the Fellowship of a Christian Social Order (FCSO). Thus, this article not only examines labour intellectuals in a Gramscian light, but seeks to challenge the claim among many historians that links between labour and Christianity collapsed before the Depression. Indeed, labour intellectuals sought to confront the prevailing hegemony of a capitalistic Christianity, not only by challenging the links the institutional churches held with the economic elite but also through developing understanding of how capitalism played an intrinsic role in the creation of sin and suffering.